Act locally, solve globally? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Policy makers everywhere are rushing to empower local communities to manage natural resources. It will not work, not unless they change the world first.. When he opened an Internet service on environmental affairs in October 1998, the Mauritian...